Britannin suppresses MCF-7 breast cancer cell growth by inducing apoptosis and inhibiting autophagy - Sadegh Rajabi; Mahboubeh Irani; Marzieh Moeinifard; Maryam Hamzeloo-Moghadam (Mashhad University of Medical Sciences, 2024)
Objective: Breast cancer is the main reason for cancer-related death in women. Britannin is a sesquiterpene lactone compound derived from Inula aucheriana with anti-tumor properties. We aimed to explore the impacts of britannin on apoptosis and autophagy in MCF-7 breast cancer cell line.Materials and Methods: The cytotoxic influences of britannin on MCF-7 cells were estimated by the MTT method. The expression levels of apoptosis-associated genes such as CASP3, BCL2, BCL2L1, STAT3, and JAK2 and transcripts of autophagy markers including ATG1, ATG4, ATG5, ATG7, ATG12, BECN1, and MAP1LC3A were quantified using quantitative real time-PCR (qRT-PCR). Western blotting method was used to evaluate the amount of caspase 3, phosphorylated JAK2, phosphorylated STAT3, ATG1, ATG4, ATG5, Beclin1, and LC-III. Results: Treatment of MCF-7 cells with various concentrations of britannin remarkably hindered the viability of these cells compared to the controls. This compound significantly elevated the expression of pro-apoptotic caspase-3 but did not influence the levels of anti-apoptotic BCL2 and BCL2L1. Britannin decreased the levels of phosphorylated forms of JAK2 and STAT3 proteins causing the blockage of the JAK/STAT pathway. Four autophagy factors expressions, including ATG4, ATG5, Beclin1, and LCIII, were reduced due to the effect of britannin on MCF-7 cells.Conclusion: Britannin triggered apoptosis in MCF-7 cells by a mechanism that led to the blockade of the JAK/STAT pathway. Moreover, britannin prohibited autophagy in these cancer cells. This may suggest britannin as an agent for the suppression of breast tumors or as an adjutant for the enhancement of anti-breast cancer drugs effect.